Response properties of spiking and non-spiking brain neurons mirror pulse interval selectivity - Zhang, Xinyang; Hedwig, Berthold (Frontiers in Cellular Neuroscience, 2022)
In the bispotted field cricket auditory pulse pattern recognition of the species-specific calling song is based on a delay-line and coincidence detection network, established by the activity and synaptic connections of only 5 auditory neurons in the brain. To obtain a more detailed understanding of the network and the dynamic of the neural activity over time we analyzed the response properties of these neurons to test patterns, in which the pulse duration was kept constant while the duration of specific pulse intervals was systematically altered. We confirm that the ascending interneuron AN1 and the local interneuron LN2 copy the structure of the pulse pattern, however with limited resolution at short pulse intervals, further evident in downstream neural responses. In the non-spiking delay-line interneuron LN5 during long pulse intervals full-blown rebound potentials develop over a time course of 35–70 ms. LN5 also reveals an overall increase in its membrane potential tuned to chirps of the calling song pulse pattern. This may contribute to the pattern recognition process by driving the activity of the coincidence-detector LN3 and may indicate a further function of the delay-line neuron LN5. The activity of LN3 and of the feature detector LN4 match the tuning of the phonotactic behavior and demonstrate an increasingly sparse coding of the calling song pulse patterns as evident in the response of the feature detector LN4. The circuitry reveals a fundamental mechanism of auditory pattern recognition and demonstrates a principle of neuronal coding.